Menyongsong Merdeka Belajar: Implementasi Konsep Kampus Merdeka Di Perguruan Tinggi - Lasino Lasino (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2021)
Higher education in Indonesia is currently facing big challenges in adapting to the needs of an ever-evolving era. The concepts of "Freedom to Learn" and "Independent Campus" are part of efforts to provide education that is relevant and responsive to the dynamics of society and industry. This article aims to investigate the implementation of these concepts in Indonesian higher education, focusing on understanding, implementation, and impact on student learning experiences.